CDK6 Immunophenotype Implicates Potential Therapeutic Application of CDK4/6 Inhibitors in Urothelial Carcinoma - Sun, Ran; Wang, Xuemei; Zhang, Leichao; Gu, Yu; Yang, Shaojuan; Wang, Liping; Wang, Xueju (Frontiers in Oncology, 2022)
Background Infiltrating bladder urothelial carcinoma is the most common bladder malignancy with limited therapeutic options and poor prognosis. Identifying new therapeutic targets or strategies has important clinical significance. The data from public sources indicate poor prognosis in urothelial carcinoma cases with high CDK6 mRNA levels. Furthermore, studies have shown that CDK6 expression is elevated in urothelial carcinoma tissue compared to the surrounding urothelium, thus presenting a case for performing CDK4/6 inhibitor targeted research in urothelial carcinoma. However, a phase II trial showed that CDK4/6 inhibitors are not effective for advanced urothelial carcinoma, suggesting that case screening is important for targeted therapy. Objective Immunohistochemistry (IHC) is simple and easy to perform and can be used to screen urothelial carcinoma cases with high CDK6 expression in clinical practice. The aim of this study was to determine the CDK6 expression threshold for positive cases. Methods We evaluated the correlation between the H-score of CDK6 protein expression and survival or CDK6 mRNA level using RNA sequencing. The effects of different CDK4/6 inhibitors were tested on bladder carcinoma cell lines with different CDK6 expression levels. Results The H-score, which predicts poor prognosis and reflects a high CDK6 mRNA level, was determined as the selection criterion for positive cases. Furthermore, we found that urothelial carcinoma cell lines with higher CDK6 expression levels displayed greater sensitivity to CDK4/6 inhibitors than cells with lower expression levels. Conclusions IHC staining for CDK6 protein in urothelial carcinoma is proposed as a promising screening platform for CDK4/6 inhibitor targeted therapy.